PSYCHOSOMATIC DISORDERS: ANCIENT AND MODERN PERSPECTIVES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Psychosomatic disorders represent a complex interplay between mind and body, where psychological factors significantly influence physical health. The concept of psychosomatic illness dates back to ancient civilizations, where disease was often viewed as a manifestation of spiritual or emotional imbalance. In modern medicine, psychosomatic disorders are recognized as conditions in which emotional stress or mental conflict leads to physiological dysfunctions. This paper explores the evolution of psychosomatic thought from ancient philosophical traditions to contemporary scientific models, focusing on mechanisms, clinical implications, and integrative approaches to treatment.